Embodied liturgy : lessons in Christian ritual - Senn, Frank C. (Minneapolis, MN : Fortress Press, 2016)
Embodied Liturgy marks a "return to the body" in thinking about Christian liturgy and sacramental practice. Rooted in phenomenology and incarnational theology, the book gives primary focus to the body as it considers the prayer offices and the liturgical calendar, sacrifices and sacraments, initiation and vestments, ritual theory and play, word and meal, fasting and feasting, penance and celebration, rites of passage, cultural perspectives, and the role of art, music, dance, and drama in worship. The author invites readers to return to the experience of their own body through guided yogic exercises. As a text for students and liturgical practitioners, the volume gives fresh voice to the experience and practice of worship as bodily acts. Embodied Liturgy is a dynamic, accessible new resource in liturgical and sacramental theology from one of the premiere scholars in the field. Frank C. Senn distills an established legacy of expertise in an innovative and inviting perspective on bodily acts of worship.
Introduction: Return to the body -- Bodies and liturgy -- Earthly bodies, earthly means -- Naked bodies, clothed bodies -- Ritual and play -- Sacrifices and meals -- Penitential bodies, celebrating bodies -- Young bodies, healthy bodies -- Sexual bodies, dead bodies -- Cultural bodies, artistic bodies -- Breathing bodies, singing bodies -- Bodies in motion -- Performing bodies.
Includes bibliographical references (pages 383-390) and index.
Keywords: Public worship; Human body -- Religious aspects -- Christianity; Liturgics; Ritual; Human body -- Religious aspects -- Christianity; Liturgics; Public worship; Ritual; Prof's picks -- 2017 -- 06 (Jun) -- Farwell